MODELING AND SIMULATION OF INDUSTRIAL FCC RISERS - Souza, J. A.; Vargas, J. V. C.; von Meien, O. F.; Martignoni, W. P. (Revista de Engenharia Térmica, 2007)
Risers are considered vital parts in Fluidized Catalytic Cracking (FCC) conversion units. It is inside the riser reactor that the heavy hydrocarbon molecules are cracked into lighter petroleum fractions such as liquified Petroleum gas (LPG) and gasoline. The FCC process is considered a key process in the world petroleum industry, since it is the main responsible for the profitable conversion of heavy gasoil into commercial valuable products. This work presents a simplified transient model to predict the response of a FCC riser reactor, i.e., the fluid flow, temperature and concentrations of the mixture components throughout the riser and at the exit. A bi-dimensional fluid flow field combined with a 6 lumps kinetic model and two energy equations are used to model the gasoil mixture flow and the cracking process inside the riser reactor. The numerical results are in good agreement with experimental data, as a result, the model can be utilized for design, and optimization of FCC units. The simulation herein presented shows the applicability of the proposed method for the numerical simulation and control of industrial riser’s units.